PENINGKATAN AKTIVITAS ENZIM LIPOPROTEIN LIPASE (LPL) DAN PERUBAHAN HISTOPATOLOGIS HATI TIKUS (Rattus norvegicus) HIPERKOLESTEROLEMIA YANG DIBERI EKSTRAK SARANG SEMUT (Myrmecodia sp.) (The Increase Activity of Lipoprotein Lipase (LPL) Enzyme and Histophatological Changes of Liver of Hypercholesterolemic Rat (Rattus norvegicus) Induced by Ethanolic Extract of Ant Plant (Myrmecodia sp.)) - R, Roslizawaty; R, Rusli; N, Nazaruddin; S, Syafruddin; Bangun, Indahlia Syahfitri; J, Jumaidar (Universitas Syiah Kuala, 2016)
This study was aimed to find out the effect of ethanolic extract of ant plant (Myrmecodia sp.) to increase the activity of enzyme lipoprotein lipase (LPL) serum and to observe the histopathological changes of hypercholesterolemic rat liver. This study used 20 male rats grouped into 4 treatment groups, namely negative control group (K1), hypercholesterolemic group (K2), and hypercholesterolemic group that administered with ethanolic extract of ant plant 100 (K3) and 200 mg/kg bw (K4). The LPL enzyme activity were measured by the titration method and histopatological changes of liver were observed by calculated fatty degeneration and fatty infiltration. The data were analyzed using one way anova followed by Duncan test. The average of LPL enzyme activity on group K1, K2, K3, and K4 were 0.800.06, 0.450.10, 0.830.11, and 0.760.03 unit, respectively. The average number of fatty degeneration on hepatocyte and fatty infiltration were 1.800.83, 3.601.14, 23.00 1.22, and 40.201.30; and 9.200.84, 16.401.14, 2.600.54, and 4.800.83, respectively. The results showed that theraphy ethanolic extract of ant plant effects significantly (P0.01) on the increase of enzyme LPL and improve liver damage in hypercholesterolemic male rats. To conclude the administration of ethanolic extract of ant plant increases the LPL enzyme activity and improves liver damage on hyperch olesterolemic rats.Key words: Myrmecodia sp., LPL activity, histopathological liver, hypercholesterolemia